2019
DOI: 10.3390/cancers11121861
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia and Sarcopenia in Older Adults with Cancer: A Comprehensive Review

Abstract: Cancer cachexia is a syndrome characterized by weight loss with accompanying loss of muscle and/or fat mass and leads to impaired patient function and physical performance and is associated with a poor prognosis. It is prevalent in older adults with cancer; age-associated physiologic muscle wasting and weakness, also known as sarcopenia, can compound deficits associated with cancer cachexia in older adults and makes studying this condition more complex in this population. Multiple measurement options are avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 100 publications
2
114
0
4
Order By: Relevance
“…Additionally, this type of exosome can participate in white adipose tissue browning and affect cancer cachexia (8), a syndrome characterized by weight loss due to muscle and/or fat loss. Cancer cachexia results in functional impairment, decreased physical ability and it is associated with a poor prognosis (89). The same mechanisms have been reported in other studies (90,91).…”
Section: Exosomes Containing Circrnas Function In Promoting or Inhibisupporting
confidence: 56%
“…Additionally, this type of exosome can participate in white adipose tissue browning and affect cancer cachexia (8), a syndrome characterized by weight loss due to muscle and/or fat loss. Cancer cachexia results in functional impairment, decreased physical ability and it is associated with a poor prognosis (89). The same mechanisms have been reported in other studies (90,91).…”
Section: Exosomes Containing Circrnas Function In Promoting or Inhibisupporting
confidence: 56%
“…The absolute reduction in macrophage number rather than relative changes in abundance remains relevant given the physiological importance of the overall immune response in repair and remodeling (59,(66)(67)(68)(69)(70). The mean age of cancer patients is ~65yrs and overlapping sarcopenic and cachectic factors along with chemotherapy may contribute to disrupted skeletal muscle immune regulation (71).Disrupted skeletal muscle repair associated with changes in macrophages has been reported with aging (38), cancer (70), and chemotherapy (53).The effects of aging on skeletal musclemacrophages has demonstrated that reloading aged skeletal muscle had a blunted hypertrophy response associated with a lower number of M1-like macrophages at baseline and blunted M1-like macrophage in ltration (early) and M2-likemacrophage transition (late) (38).Surprisingly, while in ammation is a hallmark of cancer cachexia associated with muscle weakness and fatigue (72,73), total macrophage number was reduced in damaged muscle of C26tumor-bearing mice compared to a non-cachectic tumor-bearing control (70). Additionally, macrophages were shown to regulate skeletal muscle signal transducer and activator of transcription 3 (STAT3) -downstream target of IL-6 and key regulator of skeletal muscle mitochondrial homeostasis and proteostasis(73-77)-during pancreatic cancer cachexia(78).Further work is needed to understand these potentially overlapping mechanisms with cancer and chemotherapy on skeletal muscle immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…If the metabolic shift is a consequence of decreased glucose metabolism or increased amino acid demands remains to be investigated. On the other hand, it is well known that cachexia, causing ongoing muscle loss, is an event that accompanies cancer [64]. Finally, this study identifies a range of possible markers, whose serum levels might be indicative of HCC prognosis.…”
Section: Resultsmentioning
confidence: 91%